Efficiency improvement of automatic control systems of power sources for self-contained drilling platforms - Жуков, Владимир Анатольевич; Жиленков, Антон Александрович; Безюков, Олег Константинович; Титов, Иван Леонидович (Eastern-European Journal of Enterprise Technologies, 2015)
The topical problem of ensuring stable parallel operation of two or more gas-diesel generators as a part of the self-contained power system of offshore drilling platforms and water transport facilities is considered. The operating conditions of such a system as a part of the self-contained drilling platform, where sudden changes in electric network load make it impossible to use gas-diesel generators since the latter are characterized by high instability of speed are examined. Gas-diesel generator speed depends on the load on the generator bars, which causes the need to adjust the dynamic characteristics of speed regulators of gas-diesel generators, depending on the operation mode. Analysis of the operation of the self-contained power system of the drilling rig revealed that switching processes caused by connecting or disconnecting the loads lead to fluctuations in voltage and frequency, the spectrum of which is in the same frequency range as the fluctuation spectrum of GDGS, which gives rise to the exchange fluctuations of power between parallel operating generators. Based on the experiment, the gas-diesel generator model, allowing to solve a wide range of problems concerning both management of self-contained power generation, and providing the necessary power quality indicators in power systems where the main power sources are parallel operating gas-diesel generator sets was developed. The proposed dynamic model allows to take into account non-linear properties of the gas-diesel engine, considers the operation features of the turbocharger. In addition, the model allows to reconstruct the parameters of controllers depending on the load on the shaft.